Accounting changes reporting in Malaysian corporations - Ali Khan, Mohd. Noor Azli (Penerbit UTM Press, 2009)
Changes in accounting and financial reporting are inevitable (Hall & Aldridge, 2007). Hall and Aldridge (2007) stated that this happens because in preparing periodic financial statements, companies must take estimates and judgements to allocate costs and revenues. Accounting disclosure especially notification of information on a business unit has become a widely studied area in the West (Benston, 1973). The issue of accounting change has been subject to considerable research attention during the 1990s. The main interest has been directed at exploring changes in: accounting systems, accounting techniques, the accountancy profession, and the role of an accountant (for general references to such work, see Chua (1995) and Bhimani (1996)). In Malaysia, the accounting disclosure has yet to be studied vigorously (Hamzah, 1983). This however, does not mean that this issue is unimportant, and lately a lot of researchers have been researching on the report of extraordinary item (Shamsul & Nor Izah, 2000), cash flow statement (Ng, 1999), empirical studies on accounting and disclosure (Ng, 1998), uses of financial report (Azhar, 1999) and information that are needed by consumer and voluntary disclosures by the Kuala Lumpur Stock Exchange (KLSE), currently name as Bursa Malaysia listed companies (Tan et al., 1990). Disclosure is a means whereby information regarding a business unit can be conveyed. Based on this information, interested parties and potential investors will be informed of the strengths and weaknesses of a particular business unit, in terms of profits made, and/or whether the management of the business unit act in a manner which can be of benefit to the potential investors (Hamzah, 1983). Consistency in the accounting policy as stated in the Malaysian Accounting Standards Board (MASB) 1 is one of the accounting doctrine, which is the basis of financial planning and presentation. Users should be able to compare and differentiate every company financial statement for a period of time to identify financial position flow, performance, and cash flow. For that matter, the same accounting policy will be used for an accounting period. Changes in the accounting policy need to be done if directed by the law or the MASB, or if the change will give a more accurate result for presenting a situation or transaction in a company’s financial statement (MASB 3). This study is a preliminary study on the accounting disclosure by listed companies on the main board of the KLSE based on their annual financial report. The remainder of this paper is structured as follows. The next section provides an overview of accounting change. Section three discusses research methodology, followed by research findings. The paper ends with a conclusion and directions for future research.